Simulation of SIDO flyback power converter with advanced control strategy - Win, Myint Aung (2018)
This project aims to design the advanced controller which can distribute the power based on the demand to multiple loads through the shared transformer to reduce the number of components used. With shared transformer, the power loss in the core can be significantly minimized and the cost of the overall system also greatly reduced. The focus of the project will be on using of the topology of flyback converter with advanced control strategy. One of the great benefits of using flyback converter is that it provides not only galvanic isolation for better protection of loads but also the reduced in the number of components used such as filter and inductors. As for as the scope of the project is concerned, Single Output Dual Output (SIDO) flyback converter will be used to simulate the DC-DC buck boost converter which its power distribution is governed by the Advanced controller. The controller that will be discussed and designed is the Model Predictive Voltage Controller. As the SIDO DC-DC converter shared the same transformer between loads, there will be cross regulation problem as sharing of the inductor will cause the change in voltage of one output by the load affecting another output. By utilizing MPVC, this problem can be greatly reduced as the controller can forecast the power demand of the future cycle and better distribute the power needs of the loads, thus reducing the cross-regulation problem. The simulation results have shown that the controller is able to distribute the power demand accordingly based on the set values and able to respond the step changes that is imposed on the controller.